Reviews: Dineke Schokkin. 2020. A Grammar of Paluai. The Language of Baluan Island, Papua New Guinea. Pacific Linguistics [series], vol. 663. Berlin– –Boston: De Gruyter Mouton, pp. xxv + 434 - Majewicz, Alfred f. (Lingua Posnaniensis, 2020)
[Missing]